Investing in Human Resources for Health : The Need for a Paradigm Shift - Zhao, Feng (World Health Organization, 2015)
Development partner strategies and support in the area of human resources for health (HRH) have been shaped by key reports and events over the past decade. Since 2004, when The Lancet published the Joint Learning Initiative’s call to overcome the HRH crisis, the global health community has been trying to address the critical issues surrounding HRH. The 10-year action plan on HRH proposed in The world health report 20062 and the establishment in the same year of the Global Health Workforce Alliance have drawn unprecedented attention to HRH. Thanks to a growing body of evidence,2 HRH issues have gradually made their way into the global health arena. Consensus has emerged on the “power of health workers”1 and their critical importance to health system strengthening and disease control programs.